Physiological responses of small-sided vs. regular games in youth volleyball players - Halouani, Jamel; H’mida, Cyrine; Trabelsi, Khaled; C.T Clark, Cain; Glenn, Jordan; Chtourou, Hamdi (Biology of Sport, 2023)
The aim of the present study was to evaluate the effects of two different formats of small-sided games (SSGs; 2 vs. 2 and 3 vs. 3) on physiological parameters in youth volleyball players. Twelve youth volleyball players (17.2±7.44 years, 1.89±0.6 m, 72.83±8.57 kg) completed three different games formats (regular game (RG): 6 vs. 6, SSG3: 3 vs. 3 and SSG2: 2 vs. 2). associated with two pitch dimensions (i.e., 2 vs. 2 and 3 vs. 3 on 18×4.5 m; 6 vs. 6 on 18×9 m). Each player performed 4×5 min SSG with a recovery period of 1 min between bouts. All players were members of the same youth team and played in a professional league. They had at least 6 years of volleyball training and no current injuries. This study was carried out during the competitive period. Heart rate (HR), blood lactate ([La − ]), and rating of perceived exertion (RPE) were measured. Compared to RG, physiological (i.e., HR and [La − ]) and RPE responses were significantly higher during SSG3 and SSG2 (all p < 0.05; ƞ p 2 = 0.77, ƞ p 2 = 0.65, ƞ p 2 = 0.30, respectively). Moreover, HR and RPE were significantly higher in SSG2 compared to SSG3. In contrast, no significant differences were observed in [La − ] between SSG2 and SSG3. These results suggest that the number of players influences the exercise intensity in small-sided volleyball games in youth players. Therefore, coaches could benefit from incorporating SSGs to manipulate the exercise intensity in youth volleyball players.